2020
DOI: 10.1177/2333794x20968718
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Pediatric Epilepsy Training Program for First Level Providers in Zambia

Abstract: Introduction. The developing world continues to face challenges in closing the large treatment gap for epilepsy, due to a high burden of disease and few experienced providers to manage the condition. Children with epilepsy are susceptible to higher rates of developmental impairments and refractory disease due to delays or absence of appropriate management as a result. We demonstrated that a structured education intervention on pediatric epilepsy can improve knowledge, confidence, and impact clinical practice o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The points noted will be included in the subsequent development of concepts to upscale child neurology clinician training. 17,18 The US collaboration in Armenia highlights similar issues and the need to be innovative through the onsite mentorship by visiting specialists. 19 Limitations: Our survey dissemination included a targeted sampling frame and the EPNS survey pooled data.…”
Section: Discussionmentioning
confidence: 99%
“…The points noted will be included in the subsequent development of concepts to upscale child neurology clinician training. 17,18 The US collaboration in Armenia highlights similar issues and the need to be innovative through the onsite mentorship by visiting specialists. 19 Limitations: Our survey dissemination included a targeted sampling frame and the EPNS survey pooled data.…”
Section: Discussionmentioning
confidence: 99%
“…20 A single-country evaluation of a paediatric epilepsy course from Zambia was published. 21 In 2012, the World Health Organization initiated an epilepsy training programme for non-specialist health care providers, but with only single-country evaluations published. 22,23 A study of paediatric resuscitation training reported high participant numbers (n > 13 000).…”
Section: Discussionmentioning
confidence: 99%
“…The authors used different assessments across each study 20 . A single‐country evaluation of a paediatric epilepsy course from Zambia was published 21 . In 2012, the World Health Organization initiated an epilepsy training programme for non‐specialist health care providers, but with only single‐country evaluations published 22, 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, new and innovative models are required for task sharing, education, and continuous specialty care. 13 Telemedicine can enable a continuous or semi-continuous presence of a neurologist in LMIC. The usual barrier in resource-poor settings is the lack of fast and reliable internet connections.…”
Section: Commentarymentioning
confidence: 99%
“…Thus, new and innovative models are required for task sharing, education, and continuous specialty care. 13 …”
Section: Commentarymentioning
confidence: 99%